Defensive strategies of nursing workers in the pediatric emergency room - Fabricio Alberto Lamb; Carmem Lúcia Colomé Beck; Alexa Pupiara Flores Coelho; Susan Bublitz; Fabiele Aozane; Paula Hübner Freitas (Rev Rene)
Objective: to understand the defensive strategies of nursing workers in the pediatric emergency room. Methods: this is a qualitative research carried out with nine nursing workers from a pediatric emergency roomat a federal public university hospital. The data were produced by the focus group and submitted to content thematic analysis. Results: nursing workers reported the need for emotional and affective removal from work,children and families, as well as support in the sense of “fulfilled duty” to avoid suffering. They also search for family, leisure, spirituality/religiosity, psychotherapy and support of the work team for the maintenance of well-being and mental health inside and outside the work environment. Conclusion: detachment, rationalization and the search for spaces of refuge appear as individual defensive strategies, while the collaboration and cohesion of the collective of workers represent collective defense strategies.